2020
DOI: 10.1108/jhtt-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

How smart tourism technologies affect tourist destination loyalty

Abstract: Purpose The purpose of this study is to investigate how smart tourism technologies and memorable tourism experiences affect tourist satisfaction and tourist destination loyalty. Design/methodology/approach A total of 600 questionnaires were distributed, 360 were returned (60% response rate) and a covariance-based structural equation modeling technique was used to test the hypotheses. Findings The results of this study explain that smart tourism technologies and memorable tourism experiences play essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 115 publications
(213 reference statements)
3
105
1
3
Order By: Relevance
“…Recently, smart tourism studies have turned the attention to examining the STT’s role in tourists’ travel experiences. For example, various studies focus on discovering the relationship between STT and trip expectation (Narangajavana et al, 2017 ), place experience (Azis et al, 2020 ; Chung et al, 2017 ; Tussyadiah & Fesenmaier, 2009 ), and tourist satisfaction (Narangajavana Kaosiri et al, 2019 ). In the planning phase, it is theorized that four attributes of online tourism information sources—accessibility, information reliability, interaction, and personalization—are key to planning a trip (No & Kim, 2015 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Recently, smart tourism studies have turned the attention to examining the STT’s role in tourists’ travel experiences. For example, various studies focus on discovering the relationship between STT and trip expectation (Narangajavana et al, 2017 ), place experience (Azis et al, 2020 ; Chung et al, 2017 ; Tussyadiah & Fesenmaier, 2009 ), and tourist satisfaction (Narangajavana Kaosiri et al, 2019 ). In the planning phase, it is theorized that four attributes of online tourism information sources—accessibility, information reliability, interaction, and personalization—are key to planning a trip (No & Kim, 2015 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Unforgettable travel experiences tend to exist with positive affection (Kim & Ritchie, 2014;, which means something enjoyable, in that they enjoy sharing with others in the future (Knobloch, Robertson & Aitken 2014;Zhong, Busser & Baloglu, 2017). Some found that memorable travel experiences play a crucial role in increasing tourist satisfaction and tourist loyalty (Azis, Amin, Chan & Aprilia, 2020). These suggest that the MTE implicitly stems from a satisfying psychological status, and the positively affective nature of such experience has been proved to have impacts on revisiting (Yu, Chang & Ramanpong, 2019).…”
Section: Memorable Tourism Experiencesmentioning
confidence: 99%
“…The satisfaction experienced from previous exchanges tends to increase the positive appraisal and accordingly higher possibility of repetitive purchasing. Satisfaction is an objective overall assessment of a product or service made by consumers after comparing, mainly the difference between the perceived function beforehand and the expectation afterward, which is a quantitative measure of emotion (Oliver, 1980;Fornell, 1992;Bigne et al, 2001;Azis et al, 2020). Satisfaction in the tourism industry is an emotional psychological response to the destination (Cole & Crompton, 2003).…”
Section: Satisfactionmentioning
confidence: 99%
“…Ultimately, competitiveness depends on customer satisfaction (Hardinata, et al, 2019), which is determined by the expectations of consumers towards a certain product/service and the experiences in real-time, when it comes to the delivery process (Stickdorn and Zehrer, 2009). Tourists' destination loyalty, regardless of the many loyalty measurement scales, is dependent on smart technology, as well as the unforgettable experiences, provided in the destination (Azis et al, 2020;Pai et al, 2020). Pai et al (2020) even highlighted that satisfaction with travel is positively correlated with the tourists' happiness and their intention to revisit certain destinations in the future.…”
Section: Achieving Competitive Advantage With Technologyenhanced Tourist Experiencementioning
confidence: 99%